Gastrointestinal parasites of Emu (Dromaius novaehollandiae Latham, 1790) in Ostrich Nepal Pvt. Ltd Gongoliya, Rupandehi, Nepal - Khatri, Kamala; Maharjan, Mahendra (Journal of Natural History Museum, 2018)
Ostrich and Emu farming have been lunched with a very new concept to Nepalese market for their product in which parasitic diseases may cause significant effect to their production. In order to determine prevalence of gastrointestinal parasites of Emu, a total of 100faecalsamples were collected during the month of May/July 2015. All samples were microscopically examined by using direct smear and concentration techniques (floatation and sedimentation).Out of 100 faecal samples, 65% were found positive for gastrointestinal parasites. Overall, seven different species of gastrointestinal parasites including two protozoan, three nematodes and two cestodes were recorded. Amongprotozoan parasites, Eimeria sp. (30%) was more prevalent compared to Entamoeba sp.(10%). Among helminthes parasites, Ascaris sp. (15%)showed the higher prevalence rate followed by Dromaestrogylus sp. (10%), Davainea sp.(9%), Raillietina sp. (5%) and Heterakis sp. (5%). This study suggested that parasitic infection could be a serious problem in the farm hence needed to adopt appropriate control strategies in order to strengthen the successful emu production in Nepal.